Nação, nacionalismo e território a partir da Coluna Prestes: Uma construção epistemológica geográfica crítica - Portela, Patrícia de Oliveira (2024)
Coluna Prestes (Prestes Column) bears a deep political and cultural meaning for Brazilian society. Luiz Carlos Prestes is a historical figure of importance for the devolopment of patriotic feelings. For this reason, this doctoral dissertation associates the critical thinking in geography with the political grounds of the Coluna Prestes movement. We assume that Coluna Prestes encourages a leftist, nationalist constitution based on human rights, the spread of democracy, and homeland defense. Prestes’ nationalist ideas differ from those of the right-wing parties and they focus on the needs of the working class and on the modernization of the country. As it moves, Coluna Prestes becomes a way of communicating Brazil’s territorial identity. Moving from place to place helped people realize Brazil’s territorial extent, as news came through the radio and newspapers and the literature shaped the image of the Knight of Hope. The present study is justified by framing critically the very concept of nationalism as stated by Coluna Prestes, by means of an epistemological reading based on dialectical and historical materialism in geography. The contradictions in the nationalism by Coluna Prestes and the Constitution of Brazil are also pointed out. The study relates the Coluna Prestes to nationalism and space. More specifically, it emphasizes the importance of associating Geography as critical thinking with Coluna Prestes and the role Luiz Carlos Prestes played in promoting nationalism. The research aimed at understanding how and why left-wing nationalist feeling was aroused among the members of Coluna Prestes. It also aimed at realize the role of the left-wing nationalism for the movement itself and its major effects on the Brazilian people at that time. Thus, we seek to point out the geographical features in the Brazilian historical process that comprises the organization and the effects of the Coluna Prestes from 1922 to 1927. Coluna Prestes had great importance to the relation nation-nationalism-territory, since its mobilization had an influence on the form and content of the working class movements and on the meaning of nationalism itself. Thus the Coluna’s nationalism both protected the nation and the Brazilian people, by means of social and cultural values, and aroused a nationalist feeling, by means of a “Brazilian race”. The nationalist acts aimed at both Brazilian territory and nation. The Coluna’s journey provided something one could identify with and a nationalist feeling by fighting against oppression that came from both the local ruling class and the foreign colonizing forces.